2019
DOI: 10.1002/cbf.3440
|View full text |Cite
|
Sign up to set email alerts
|

AMPK α1 mediates the protective effect of adiponectin against insulin resistance in INS‐1 pancreatic β cells

Abstract: The fat-derived protein adiponectin is known to reverse the effects of insulin resistance and to lower blood glucose levels. The AMP-activated protein kinase (AMPK) signalling pathway plays a central role in metabolism and energy homeostasis.Here, to investigate the role of AMPK in the protective effect of adiponectin against insulin resistance, we established the model of high-glucose (HG)-and high-lipid (HL)-induced insulin resistance in INS-1 pancreatic β cells. We found that 25mM of glucose and 0.4mM of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…aPn, an adipocyte-derived secretory protein, plays an important role in metabolic (31), anti-inflammatory (32) and anti-oxidative activities (33). a number of studies have reported that aPn also specialized in alleviating myocardial, renal and pancreatic ischemic reperfusion injury by reducing apoptosis (34)(35)(36). our previous study indicated that aPn reduced the number of apoptotic activities from neurons following Gcir induced by ca-cPr (30).…”
Section: Discussionmentioning
confidence: 99%
“…aPn, an adipocyte-derived secretory protein, plays an important role in metabolic (31), anti-inflammatory (32) and anti-oxidative activities (33). a number of studies have reported that aPn also specialized in alleviating myocardial, renal and pancreatic ischemic reperfusion injury by reducing apoptosis (34)(35)(36). our previous study indicated that aPn reduced the number of apoptotic activities from neurons following Gcir induced by ca-cPr (30).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a large number of studies have also shown that regulating the production of adipocytokines or the expression of adipocyte-specific genes was one of the most effective approaches to improve IR. For example, adiponectin, as a cytokine secreted by adipocytes, was a specific cytokine of adipocytokines that is most closely related to IR and has the effect of regulating lipid metabolism in the liver ( Caselli 2014 ; Wang et al, 2019 ). Adiponectin could improve insulin sensitivity when it binds to the adiponectin receptor (AdipoR1/2).…”
Section: Fatty Liver Diseasementioning
confidence: 99%
“…Adiponectin could improve insulin sensitivity when it binds to the adiponectin receptor (AdipoR1/2). Furthermore, adiponectin could activate AMPK activity, which in turn enhances insulin signal transduction of adipose cells, reverses IR, and inhibits the occurrence and development of NAFLD ( Wang et al, 2019 ; Yang et al, 2022 ). Therefore, AMPK may be a potential new target for the prevention and treatment of NAFLD.…”
Section: Fatty Liver Diseasementioning
confidence: 99%
“…PRKAA1 is the α-subunit of 5-AMP-activated protein kinase (AMPK), which functions as an energy sensor and plays a key role in maintaining cellular metabolic homeostasis (Roa, et al 2018, Wang, et al 2019).…”
Section: Discussionmentioning
confidence: 99%